The mechanism study of miR‐125b in occurrence and progression of multiple myeloma - Gao, Da (Cancer Med, 2017)
Although many efforts have contributed to improve our knowledge of molecular pathogenesis about multiple myeloma (MM), the role and significance of microRNAs and long noncoding RNAs in MM cells, along with the core mechanism remains virtually absent. The mRNA levels of miR‐125b and MALAT1 in MM cell lines were detected by qRT‐PCR. The influence of Lenti‐Sh‐miR‐125b on cell viability and the Notch‐1 pathway‐related proteins were assessed by MTT method and western blot, respectively. We also investigated the regulation effect between MALAT1 and Notch1 pathway. Moreover, the connection between Notch1 signaling and MM cell growth was discussed in‐depth. The reverse effect of pcDNA‐Notch1 on the cell viability and Notch‐1 pathway proteins induced by Si‐MALAT1 was also studied. Furthermore, miR‐125b overexpressing MM cell lines were injected subcutaneously into nude mice. MiR‐125b and MALAT1 were inversely expressed in MM cell lines. Lenti‐Sh‐miR‐125b inhibited the expression of MALAT1 and Notch‐1 protein. Binding sites were confirmed between miR‐125b and MALAT1, and silencing MALAT1 did not alter the expression of Notch‐1. The apoptosis rate was increased and the survival rate was decreased obviously in GSI XII (targeted cleavage of Notch‐1 receptor) group, along with the inhibited Notch1 and HES1 proteins. Moreover, the decreased cell viability and Notch‐1 pathway proteins induced by Si‐MALAT1 could be reversed by pcDNA‐Notch1. Lenti‐Sh‐miR‐125b promoted survival and decreased Notch1 and HES1 proteins levels, while this effect was reversed by si ‐MALAT1. MiR‐125b regulated MALAT1 expression via Notch1 signaling pathway to regulate cell growth, thus participating in the occurrence and progression of MM, which functioned as a therapeutic target for tracking MM.